2017
DOI: 10.15252/embj.201696307
|View full text |Cite
|
Sign up to set email alerts
|

Fam60a defines a variant Sin3a‐Hdac complex in embryonic stem cells required for self‐renewal

Abstract: Sin3a is the central scaffold protein of the prototypical Hdac1/2 chromatin repressor complex, crucially required during early embryonic development for the growth of pluripotent cells of the inner cell mass. Here, we compare the composition of the Sin3a-Hdac complex between pluripotent embryonic stem (ES) and differentiated cells by establishing a method that couples two independent endogenous immunoprecipitations with quantitative mass spectrometry. We define the precise composition of the Sin3a complex in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 89 publications
2
70
0
Order By: Relevance
“…To determine the set of genes affected by both Pali1 and Aebp2, we took the top three thousand H3K27me3 positive genes and computed the intersection of those genes that lose H3K27me3 in the Pali1/2 double knockout and gain H3K27me3 in the Aebp2 gene trap. Data for H3K27me3 was taken from GSE81081 and processed as previously described (Streubel et al, 2017). In brief, reads were aligned to the mouse reference genome (mm10) using Bowtie2 v2.1.0 (Langmead and Salzberg, 2012) and peaks determined using macs2 v2.1.1 (Feng et al, 2012).…”
Section: Continuedmentioning
confidence: 99%
“…To determine the set of genes affected by both Pali1 and Aebp2, we took the top three thousand H3K27me3 positive genes and computed the intersection of those genes that lose H3K27me3 in the Pali1/2 double knockout and gain H3K27me3 in the Aebp2 gene trap. Data for H3K27me3 was taken from GSE81081 and processed as previously described (Streubel et al, 2017). In brief, reads were aligned to the mouse reference genome (mm10) using Bowtie2 v2.1.0 (Langmead and Salzberg, 2012) and peaks determined using macs2 v2.1.1 (Feng et al, 2012).…”
Section: Continuedmentioning
confidence: 99%
“…Using a proteomics approach, a recent study identified SIN3-HDAC Complex Associated Factor (FAM60A, also known as SINHCAF) as a new ESC-specific subunit of the Sin3a-HDAC complex (Streubel et al, 2017). FAM60A colocalizes genome-wide with other complex members at promoters and is required for SIN3A localization.…”
Section: Histone Deacetylasesmentioning
confidence: 99%
“…3). O-GlcNAcylation is thought to be involved in key cellular processes such as gene regulation and expression [22][23][24], metabolic activity [25], and cellcycle regulation [26]. Changes in O-GlcNAc homoeostasis have been linked to severe developmental problems and neurodegenerative diseases [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%